1990
DOI: 10.1093/infdis/162.1.39
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Promoter of Cell Differentiation and Selected Hormones on Human Cytomegalovirus Infection Using an In Vitro Cell System

Abstract: The influence of factors that can regulate cellular developmental or metabolic processes in host tissue on cytomegalovirus (CMV) replication in vitro was determined. Hydrocortisone treatment of cells before viral infection resulted in a 12- to 13-fold increase in the expression of immediate early proteins at 4 h after virus inoculation. The addition of a phorbol diester 1.5 h after CMV infection resulted in an 8- to 13-fold increase in production of viral progeny. In contrast, beta-human chorionic gonadotropin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 26 publications
1
22
0
1
Order By: Relevance
“…It has been suggested that productive CMV infection is suppressed in early gestation, and the suppressive effect wanes with advancing gestation [Stagno et al, 1975;Stagno, 1995]. In addition, transient depression of maternal humoral or cell-mediated immune responses to CMV during late pregnancy [Faix et al, 1983;Kumar et al, 1984] and hormonal changes during gestation [Tanaka et al, 1984;Mackowiak et al, 1987;Forbes et al, 1990] are suggested to enhance the reactivation of latent CMV Fig. 1.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that productive CMV infection is suppressed in early gestation, and the suppressive effect wanes with advancing gestation [Stagno et al, 1975;Stagno, 1995]. In addition, transient depression of maternal humoral or cell-mediated immune responses to CMV during late pregnancy [Faix et al, 1983;Kumar et al, 1984] and hormonal changes during gestation [Tanaka et al, 1984;Mackowiak et al, 1987;Forbes et al, 1990] are suggested to enhance the reactivation of latent CMV Fig. 1.…”
Section: Discussionmentioning
confidence: 99%
“…55 Similarly, cyclosporine use has been associated with CMV disease in some studies, but there are no data available to disentangle the medication from the patients with severe disease in whom it is used. Infliximab has not been associated with an increased risk of CMV reactivation in patients with IBD.…”
Section: How Frequently Is CMV Detected In the Colon Of Patients Withmentioning
confidence: 99%
“…Many investigators have reported that cellular differentiation by the addition of chemicals or cytokines such as phorbol esters, DMSO, retinoic acid, hydrocortisone, concanavalin A, dimethylacetimide, sodium valproate, β-gonadotropin, nerve growth factor or dbcAMP is necessary to induce permissive CMV infection or to increase CMV gene expression and virus replication in primary cells and cell lines (Dutko & Oldstone, 1981 ;Tanaka et al, 1985Tanaka et al, , 1991La Femina & Hayward, 1986 ;Weinshenker et al, 1988 ;Forbes et al, 1990 ;Ibanez et al, 1991 ;Turtinen & Seufzer, 1994 ;Kuntz-Simon & Obert, 1995). Here, we report that pretreatment of the oligodendrocyte cell line HOG with either PMA or dbcAMP\IBMX permitted infection with CMV as judged by the expression of the early and late CMV genes and release of extracellular infectious CMV particles.…”
Section: Discussionmentioning
confidence: 99%